Public participation and willingness to cooperate in common-pool resource management: a field experiment with fishing communities in Brazil - Carina Cavalcanti; Felix Schläpfer; Bernhard Schmid (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2008)
The primary evidence about the factors determining successful self-governance of common-pool resources (CPR) has come from case studies. More recently, this observational evidence has been complemented by insights from economic experiments. Here we advance a third approach in which the role of local deliberation about the management of a fishery resource is investigated in a field experiment. Using three control and three treatment communities in a freshwater fishery, we tested if participation in developing specific measures for community-based sustainable CPR management increased the willingness to contribute to the implementation of these measures. Each community was also exposed to information about their community leader's advice about the proposed measures. Both participation and leader advice affected the willingness of participants to contribute to one of three concrete proposals. However, the strongest influence on individual willingness to contribute was exerted by the individual beliefs about the cooperation of others in CPR management.
Keywords: 330; local deliberation; participatory research; willingness to contribute; beliefs; fishing resources; field experiment